An Assessment of Parental Involvement on Public Secondary School Adolescents’ Academic Performance in Sciences, in Lagos State, Nigeria - Odeyemi, Bamidele Segun Donald (Edukasiana: Jurnal Inovasi Pendidikan, 2024)
The study examined the assessment of parental involvement on secondary school adolescents’ academic performance in sciences in senior secondary schools, in Mushin Local Government Area of Lagos State. In this study, some relevant and extensive literature were reviewed under relevant sub-headings. The descriptive research survey was used to assess the respondents’ opinions using the researcher-made questionnaire. The sample for the study was achieved through systematic sampling technique. In this study, 120 (one hundred and twenty) respondents were randomly selected and used as samples to represent the population of the study. A total of three (3) null hypotheses were formulated and tested in this study. Also, the independent t-test statistical tool was used to test and analyze the null hypotheses at 0.05 level of significance. The three hypotheses were tested and accepted to have significant importance on adolescents’ academic performance.